(untitled) (Economic and Political Thought, 2019)
Libya is a country plunged in chaos. Fighting is ongoing in many regions in the North. In the north-western part of the country a strong position is held by coalition of Islamists. The political situation in Libya is extremely complicated. On the 18th December 2015 the members of the House of Representatives and the General National Congress signed a Libyan Political Agreement. As a result a Presidential Council and the Government of National Accord (GNA) were created. The House of Representatives still exists as a legislative body and the Advisory Board, known as the High Council of State. In fact, the Libyan Government is still divided between the House of Representatives and a General National Congress (GNC), as two separate governments. One of them – the House of Representatives, has its headquarters in Tripoli, the capital that is controlled by the Islamists, while the second is a General National Congress, in Tobruk.